Introducing maximum sustainable yield targets in fisheries could enhance global food security - Christian Elleby; Ignacio Pérez Domínguez; Rasmus Nielsen; Max Nielsen; Ayoe Hoff (Communications Earth & Environment)
Abstract Aquatic foods are crucial for global food and nutrition security, but overfishing has led to depleted fish stocks, threatening both food security and the environment. Here, we combine a fish stock model with a global agriculture and food market model in order to analyze scenarios involving a continuation of current fishing trends versus optimal management through maximum sustainable yield targets. Maximum sustainable yield management of overfished stocks could increase yields by 10.6 Megatons, equivalent to 12% of total catches and 6% of aquatic animal production in 2022. This would alleviate the need for aquaculture expansion by an equivalent of 3 years of growth in the aquaculture sector at its current level, and reduce meat and feed demand. Lower food prices and additional supply could enhance global food security. Conversely, continued overfishing will likely lead to lower catches over time, adding pressure to the agricultural and aquaculture sectors. Although maximum sustainable yield management is not a panacea, it represents a positive step towards achieving sustainable food production.